Research methodology for social sciences - Acharyya, Rajat; Bhattacharya, Nandan, 1968- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
'Research Methodology for Social Sciences provides guidelines for designing and conducting evidence-based research in social sciences and interdisciplinary studies using both qualitative and quantitative data. Blending the particularity of different sub-disciplines and interdisciplinary nature of social sciences, this volume: Provides insights on epistemological issues and deliberates on debates over qualitative research methods; Covers different aspects of qualitative research techniques and evidence-based research techniques including survey design, choice of sample, construction of indices, statistical inferences, and data analysis; Discusses concepts, techniques, and tools at different stages of research beginning with design of field surveys to collect raw data and then to analyze the data using statistical and econometric methods; With illustrations, examples and a reader friendly approach, this volume will serve as a key reference material for compulsory research methodology courses at Doctoral levels across different disciplines like Economics, Sociology, Women's Studies, Education, Anthropology, Political Science, International Relations, Philosophy, History, Business Management and the like. This volume will also be indispensable for post-graduate courses dealing with quantitative techniques and data analysis'--
Includes bibliographical references.
Buku bacaan asas Institut Islam Hadhari.
Keywords: Social sciences -- Methodology; Qualitative research -- Philosophy